Acylation/cyclization of 1, 6-dienes with ethers under catalyst- and base-free conditions. Issue 12 (8th June 2020) - Huang, Xun-Jie; Qin, Fu-Hua; Liu, Yi; Wu, Shi-Ping; Li, Qiang; Wei, Wen-Ting
Abstract : A concise and eco-friendly acylation/cyclization of 1, 6-dienes with linear ethers under catalyst- and base-free conditions has been developed. Abstract : A concise and eco-friendly acylation/cyclization of 1, 6-dienes with linear ethers under catalyst- and base-free conditions has been developed. tert -Butyl hydroperoxide (TBHP)-promoted tandem cleavage of C(sp 3 )–H and C(sp 3 )–O bonds of linear ethers is the key in this process, which provides a straightforward and efficient method to realize acylation reaction. The significant advantages of this method include catalyst- and base-free, mild reaction conditions, high scalability, operational simplicity, ease of scale-up, dual roles of ethers and controllable synthesis.